Alone in the Mind: Review of Research Examining the Link Between Loneliness and Dementia - Ahmed Hussein Al‐Samiry; Samer Imad Mohammed; Ahmed Majid Hammed; Tayf M. Maryoosh (Medicine Advances)
ABSTRACT This narrative review focused on research investigating the impact of loneliness on the prevalence of dementia and its relationship with other risk factors. A comprehensive and rigorous search was conducted using a variety of scientific databases with specific keywords to identify all prior studies that examined the correlation between dementia and loneliness. The inquiry was confined to articles published in English from January 2017 to March 2024. The narrative review identified a consensus regarding the role of loneliness in enhancing the risk of all‐cause dementia, with a particular emphasis on the subjective perception of loneliness. This phenomenon may be caused by the sensations of exclusion, discrimination, and alienation that are typically associated with low self‐esteem and low life satisfaction, which may contribute to cognitive impairment and depressive symptoms. This finding was obtained despite the absence of robust evidence regarding the involvement of loneliness in the pathogenesis of dementia. Existing research has not yet identified a correlation between hereditary factors that influence the development of dementia and feelings of loneliness. However, loneliness is strongly associated with depression, which is a potential risk factor for dementia. Previous studies have reported a moderate correlation between depression and loneliness, as individuals who are isolated and lack a sense of community exhibit higher levels of depression. Meditation, social cognitive training, and social support are three strategies that have been implemented to address loneliness and are reported to be the most effective interventions. A strong correlation exists between dementia and loneliness. Although such strategies are unlikely to impede the progression of the disease if cognitive deterioration is already underway, understanding these associations can assist in the development of strategies to alleviate the effects of loneliness on vulnerable individuals.